2010
DOI: 10.1051/0004-6361/201014059
|View full text |Cite
|
Sign up to set email alerts
|

MML 53: a new low-mass, pre-main sequence eclipsing binary in the Upper Centaurus-Lupus region discovered by SuperWASP

Abstract: We announce the discovery of a new low-mass, pre-main sequence eclipsing binary, MML 53. Previous observations of MML 53 found it to be a pre-main sequence spectroscopic multiple associated with the 15-22 Myr Upper Centaurus-Lupus cluster. We identify the object as an eclipsing binary for the first time through the analysis of multiple seasons of time series photometry from the SuperWASP transiting planet survey. Re-analysis of a single archive spectrum shows MML 53 to be a spatially unresolved triple system o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…In some spectra we also observed a faint, stationary third peak between the primary and secondary peaks, consistent with the presence of a third component in the system first noted by Torres et al (2006) and confirmed by Hebb et al (2010). As this peak could not be unambiguously identified in all of our observations, we did not attempt to derive radial velocities for this component.…”
Section: Radial Velocitiessupporting
confidence: 79%
See 4 more Smart Citations
“…In some spectra we also observed a faint, stationary third peak between the primary and secondary peaks, consistent with the presence of a third component in the system first noted by Torres et al (2006) and confirmed by Hebb et al (2010). As this peak could not be unambiguously identified in all of our observations, we did not attempt to derive radial velocities for this component.…”
Section: Radial Velocitiessupporting
confidence: 79%
“…A very low S /N in the observation of Julian Date 2 454 971 prevented a clear cross-correlation function for that night; consequently, it was not used in the spectroscopic analysis, leaving 12 nights with usable data. Our cross-correlation functions for MML 53 typically show two distinct peaks, corresponding to the two eclipsing components, whose velocities vary in time with the orbital period determined from the discovery light curve of Hebb et al (2010).…”
Section: Radial Velocitiesmentioning
confidence: 95%
See 3 more Smart Citations